Оценки основных характеристик алгоритмов вычисления частотной характеристики линейной стационарной модели объекта управления на некоторых классах функций - Задирака, В.К.; Коломыс, Е.Н.; Луц, Л.В.; Мельникова, С.С. (Проблемы управления и информатики, 2014)
Побудовано ефективні за точністю алгоритми наближеного обчислення частотної характеристики лінійної моделі об’єктів керування з постійними параметрами на класах функцій різного степеня гладкості та отримано оцінки їх основних характеристик (точності та швидкодії). Розглянуто також найбільш наближені до практики інтерполяційні класи функцій. The article is devoted to the construction of effective with respect to accuracy algorithms of approximate calculation of frequency characteristic of linear model of controlled objects with permanent parameters on classes of functions of varying degrees of smoothness and provide estimates of their main characteristics (accuracy and speed). Also the most approximate to the practice of the interpolation function classes are considered.